Reproducing kernel method for the solutions of non-linear partial differential equations - Yildirim, Elif Nuray; Akgül, Ali; İnç, Mustafa (Taylor and Francis Ltd., 2021)
In modeling of a lots of complex physical problems and engineering process, the non-linear partial differential equations have a very important role. Development of dependable and effective methods to solve such types equations are constructed. In the suggested technique, reproducing kernel method is examined to approximate the solutions together with reproducing kernel functions. In order to demonstrate accuracy, the performance and reliability of the proposed method, the results of the experiments and the available results are compared. There is high stability for a higher degree of accuracy between the solutions. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group on behalf of the University of Bahrain.
Keywords: bounded linear operator; Hilbert spaces; partial differential equations; Reproducing kernel functions